Integration of transcriptomics and metabolomics reveals toxicological mechanisms of ZhuRiHeng drop pill in the 180-day repeated oral toxicity study - Zhang, Qian; Wang, Fang; Liu, Jing; Li, Jun; Zhang, Wei; Na, Shengsang; Lu, Jingkun; Wang, Yuewu (Frontiers in Pharmacology, 2024)
Background: ZhuRiHeng Drop Pill (ZRH) is a traditional Mongolian medicinal preparation.Despite its long history of use for the treatment of coronary heart disease, there have been few toxicological studies of the safety profile of ZRH.In order to comprehensively elucidate the underlying mechanisms behind the observed toxicity of ZRH on rat livers in the 180-day repeated oral toxicity study, we conducted a comprehensive analysis by integrating transcriptomic and metabolomic data.Methods: High-resolution mass spectrometry was conducted to evaluate the constituents of ZRH. For the acute oral toxicity study, mice were administered a dose of 32 g/(kg•d) of ZRH, while rats were instead orally administered 0.934, 1.868, or 3.736 g/(kg•d) of ZRH over a 180-day period in a 180-day repeated oral toxicity study. Conventional index and organ weights/histology were then monitored to detect any potential ZRH treatment-related toxicity.To identify key genes and metabolites involved in ZRH toxicological processes, we performed transcriptomic and metabolomic analyses of liver tissue upon ZRH treatment using RNA-seq techniques, qPCR and liquid chromatography-mass spectrometry analyses.Results: A total of 60 compounds in ZRH were identified and speculated in positive and negative ion modes. Mice in the acute toxicity study exhibited no signs of ZRH-related toxicity. In a protracted oral toxicity investigation spanning 180 days, discernible elevations in liver ratios were noted in both male and female rats across all three dose cohorts, relative to the control group (P ＜ 0.05 or P ＜ 0.01). Upon subjecting to ZRH treatment, our transcriptomic and qPCR analyses unveiled notable up-regulation of crucial genes, exemplified by Abcb1b and Cyp2b2, known for theirs involvement in liver drug transport and metabolism function. Furthermore, our untargeted metabolomic analysis provided supplementary insights, revealing significant regulation in pyrimidine metabolism, as well as alanine, aspartate, and glutamate metabolism pathways.Our study unveils a panoramic understanding of the temporal, dosage-specific, and gene dimensions surrounding the metabolic and transcriptional shifts induced by ZRH exposure. As we peer into the future, recommendations emerge for further exploration, encompassing aspects such as time dynamics, dosage considerations, and gene-centric avenues to enhance therapeutic efficacy.